Atypical Employment Relations in Brazil After the Labor Reform - Zbucka-Gargas, Marta; da Rocha, Cláudio Iannotti (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The purpose of this publication is to provide an overview of labor law changes in Brazil that have significantly affected fundamental employment principles. Laws 13.427/17 and 13,467/17, collectively known as the Labor Reform, introduced atypical forms of employment, heavily modifying individual and collective labor laws. In particular, the changes include: employment in the form of intermittent work, telework, outsourcing or hyper-sufficient workers. The labor law reform, which has been carried out, introduces a number of novelties into the Brazilian legal system and raises many questions and doubts. There are concerns about whether the regulation undermines the existing legal order and thus threatens the dignity of workers, their physical and mental health, as well as negatively affects the working environment.